Impacts of environment on the sudden track change of super typhoon GAEMI(2024) - Ma, Yiming; Qiu, Hui; Feng, Baofei; Qi, Haixia; Zhang, Jun; Gong, Wenting; Liu, Jing (Frontiers in Earth Science, 2025)
To improve understanding of essential aspects that influence forecasting of tropical cyclone sudden track change, by using ERA5 reanalysis data provided by the European Centre for Medium-Range Weather Forecasts (ECMWF), the synoptic analysis method and the vorticity diagnosis method to explore the reasons for the sudden track change of super typhoon GAEMI(2024). It is found that the subtropical high on the east of the typhoon and the trough on the north are the main synoptic systems affecting the sudden track change. Due to the uneven distribution of the wind field in the vertical direction and the uneven horizontal distribution of vertical motion, the vertical motion tilts the horizontal vorticity to generate a vertical vorticity component. Thus the vorticity tilting term is the main reason for the enhancement of the subtropical high. During the eastward movement of the trough on the north side of the typhoon, its intensity weakened and the bottom of the trough moved northward. And at the same time, the typhoon intensity weakened after landfall, so the westward-extending subtropical high formed a steadily maintained high-pressure dam in the north of the typhoon. Under the combined effect of the above changes in the environmental field, the meridional steering current of the typhoon decreases rapidly, and under the guidance of the upper-level steering flow, the typhoon suddenly turns westward from the northwestward track.